Race, ethnicity, community-level socioeconomic factors, and risk of COVID-19 in the United States and the United Kingdom. (August 2021) - Lo, Chun-Han; Nguyen, Long H.; Drew, David A.; Warner, Erica T.; Joshi, Amit D.; Graham, Mark S.; Anyane-Yeboa, Adjoa; Shebl, Fatma M.; Astley, Christina M.; Figueiredo, Jane C.; Guo, Chuan-Guo; Ma, Wenjie; et al.
Abstract: Background: There is limited prior investigation of the combined influence of personal and community-level socioeconomic factors on racial/ethnic disparities in individual risk of coronavirus disease 2019 (COVID-19). Methods: We performed a cross-sectional analysis nested within a prospective cohort of 2, 102, 364 participants from March 29, 2020 in the United States (US) and March 24, 2020 in the United Kingdom (UK) through December 02, 2020 via the COVID Symptom Study smartphone application. We examined the contribution of community-level deprivation using the Neighborhood Deprivation Index (NDI) and the Index of Multiple Deprivation (IMD) to observe racial/ethnic disparities in COVID-19 incidence. ClinicalTrials.gov registration: NCT04331509. Findings: Compared with non-Hispanic White participants, the risk for a positive COVID-19 test was increased in the US for non-Hispanic Black (multivariable-adjusted odds ratio [OR], 1.32; 95% confidence interval [CI], 1.18–1.47) and Hispanic participants (OR, 1.42; 95% CI, 1.33–1.52) and in the UK for Black (OR, 1.17; 95% CI, 1.02–1.34), South Asian (OR, 1.39; 95% CI, 1.30–1.49), and Middle Eastern participants (OR, 1.38; 95% CI, 1.18–1.61). This elevated risk was associated with living in more deprived communities according to the NDI/IMD. After accounting for downstream mediators of COVID-19 risk, community-level deprivation still mediated 16.6% and 7.7% of the excess risk in Black compared to White participants in the US and the UK, respectively. Interpretation: Our results illustrate the critical role of social determinants of health in the disproportionate COVID-19 risk experienced by racial and ethnic minorities. Funding: Please refer to the Funding section at the end of the article.